The Frequency and Severity of Nausea and Vomiting during Pregnancy and its Association with Psychosocial Health - Fatemeh Bazarganipour; Hamid Mahmoodi; Beheshteh Shamsaee; Abdolvahab Taghavi (Journal of Midwifery & Reproductive Health, 2015)
Background & aim: The present study aimed to evaluate  the frequency and severity of nausea and vomiting during pregnancy (NVP) and to investigate the association between psychosocial health and the severity of NVP. Methods:This cross-sectional study was performed on 200 eligible pregnant women with nausea and vomiting at three prenatal care centers in Kashan, Iran. The participants completed demographic and pregnancy-related questionnaire, Beck Depression Inventory-Short Form, Winnfield Tiygmann social support questionnaire and Paykel scale of stressful life events. the severity of NVP was also recorded. ANOVA and Kruskal-Wallis tests were used to determine the relationship between different variables. P-value less than 0.05 was considered statistically significant. Results: The frequency of NVP was estimated at 71.5%. In total, 19%, 45.5% and 7% of these cases had mild, moderate and severe NVP, respectively. The severity of NVP was significantly associated with depression level (P=0.01). However, there was no correlation between the level of social support and unpleasant life events with severity of NVP. Conclusion: According to the results of this study women with more severe NVP experienced a higher level of depression, compared to others. However, social support and other factors were not correlated with the severity of NVP.